Karen Symms Gallagher: CAEP Chair Shares Insight into Teacher Preparation, Accreditation - Lori Goodson (Educational Considerations, 2018)
At the heart of teacher preparation, changes are taking place—a push for continued high standards and an effort to determine the impact various programs are having on P-12 student learning. Leading the way is the Council for the Accreditation of Educator Preparation (CAEP), which emerged in 2010 from education leaders’ desire for a next generation of accreditation model to improve the preparation of teachers for America’s schools. In this challenging environment, Karen Symms Gallagher, the Emery Stoops and Joyce King Stoops Dean of the University of Southern California (USC) Rossier School of Education shares her insight as the recently selected chair of the CAEP Board of Directors. Gallagher has been a steady presence in the ever changing world of teacher preparation.
Keywords: CAEP; teacher preparation; accreditation; standards; Karen Symms Gallagher; USC; NCATE